Sexting as a Predictor of First-Time Sexual Behavior Among At-Risk Early Adolescents. (April 2023) - Bogner, Jaclyn; Hadley, Wendy; Franz, Daschel; Barker, David H.; Houck, Christopher D.
"Sexting" (electronic transmission of sexual pictures/messages) among early adolescents is associated with early sexual activity, a marker of increased sexual risk. The current study is a secondary analysis that examined the longitudinal relationship between sexting and first-time sex among a sample of early adolescents deemed "at risk" due to behavioral or emotional problems. Adolescents participated in a longitudinal sexual risk prevention trial and completed questionnaires assessing demographics, unsupervised peer time, mental health, and participation in sexting, oral sex, and penetrative sex (vaginal/anal). Analyses included 343 early adolescents ( M age = 12.89, 51% female, 77% racial/ethnic minority) with no history of oral or penetrative sex. Those who reported sexting at baseline were more likely to report first-time oral and/or penetrative sex by the 1-year follow-up. Exploratory analyses revealed that sexting predicted those who had engaged in both oral and penetrative sex. These findings highlight the need to address sexting in risk prevention.